1998
DOI: 10.1111/j.1469-8137.1998.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic nitrogen fixation is confined to a subset of cells in the non‐heterocystous cyanobacterium Symploca PCC 8002

Abstract: Symploca PCC 8002 Ku$ tzing is a filamentous cyanobacterium that lacks the specialized cells, known as heterocysts, that protect nitrogenase from O # in most aerobic N # -fixing cyanobacteria. Nevertheless, Symploca is able to carry out N # fixation in the light under aerobic conditions. When cultures were grown under light\dark cycles, nitrogenase activity commenced and increased in the light phase and declined towards zero in the dark. Immunolocalization of dinitrogenase reductase in sectioned Symploc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Symploca PCC8002 was originally isolated from tidal sediment and assigned as Microcoleus chthonoplastes. Fredriksson et al (1998) reported that nitrogenase activity in this organism was confined to the light and showed that nitrogenase was present in a subset of the cells similar to the supposed diazocytes of Trichodesmium. However, this pattern may not be a general characteristic of this genus (Kumazawa et al 2001).…”
Section: N 2 -Fixing Cyanobacteriamentioning
confidence: 97%
“…Symploca PCC8002 was originally isolated from tidal sediment and assigned as Microcoleus chthonoplastes. Fredriksson et al (1998) reported that nitrogenase activity in this organism was confined to the light and showed that nitrogenase was present in a subset of the cells similar to the supposed diazocytes of Trichodesmium. However, this pattern may not be a general characteristic of this genus (Kumazawa et al 2001).…”
Section: N 2 -Fixing Cyanobacteriamentioning
confidence: 97%
“…This pattern has been reported for only 2 other cyanobacteria, Lyngbya majuscula and Symploca sp. (Jones 1990, Fredriksson et al 1998. Trichodesmium is very abundant and is recognized as one of the most important nitrogen fixers in tropical and subtropical oligotrophic oceans (Capone et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…1). Active photosynthetic components (such as PSI and PSII complexes, Rubisco, carboxysomes) are found in all cells, even those harboring nitrogenase (Janson et al 1994;Fredriksson et al 1998;Berman-Frank et al 2001a). Hence, spatial aggregation of nitrogenase into certain zones (or cells) is not sufficient to protect against oxygen.…”
mentioning
confidence: 99%